2021
DOI: 10.3390/ijms22020901
|View full text |Cite
|
Sign up to set email alerts
|

From Posttranslational Modifications to Disease Phenotype: A Substrate Selection Hypothesis in Neurodegenerative Diseases

Abstract: A number of neurodegenerative diseases including prion diseases, tauopathies and synucleinopathies exhibit multiple clinical phenotypes. A diversity of clinical phenotypes has been attributed to the ability of amyloidogenic proteins associated with a particular disease to acquire multiple, conformationally distinct, self-replicating states referred to as strains. Structural diversity of strains formed by tau, α-synuclein or prion proteins has been well documented. However, the question how different strains fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 90 publications
(231 reference statements)
0
11
0
Order By: Relevance
“…Recent studies have identified conformational variants of α‐Syn strains that exhibit distinct neurotoxicity and seeding activity, which may contribute to the clinical and pathological heterogeneity of synucleinopathies 50‐54 . The formation of different strains is believed to be controlled by posttranslational modification of α‐Syn, such as phosphorylation and truncation 55 . Here we show that 27‐OHC accelerates the fibrillization of α‐Syn and alters the biochemical properties of the resultant fibrils.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Recent studies have identified conformational variants of α‐Syn strains that exhibit distinct neurotoxicity and seeding activity, which may contribute to the clinical and pathological heterogeneity of synucleinopathies 50‐54 . The formation of different strains is believed to be controlled by posttranslational modification of α‐Syn, such as phosphorylation and truncation 55 . Here we show that 27‐OHC accelerates the fibrillization of α‐Syn and alters the biochemical properties of the resultant fibrils.…”
Section: Discussionmentioning
confidence: 54%
“…[50][51][52][53][54] The formation of different strains is believed to be controlled by posttranslational modification of α-Syn, such as phosphorylation and truncation. 55 Here we show that 27-OHC accelerates the fibrillization of α-Syn and alters the biochemical properties of the resultant fibrils. The 27-OHC PFFs show enhanced seeding activity and neurotoxicity compared with the pure α-Syn PFFs.…”
Section: Discussionmentioning
confidence: 66%
“…In the context of conformational diversity, post-translational modifications (PTMs) also represent a potential structural constraint present in vivo that is not available to direct amyloid assembly in vitro. A range of PTMs are known to affect amyloid-related disease states [ 64 ]. For example, sialylation of PrP is emerging as a substantial driver of prion pathogenesis [ 65 ] and as such may represent a selective constraint on conformations that can propagate in vivo, potentially defined by a balance between hindering conversion of monomer into protofibrils and protecting assembled protofibrillar structures from destruction by cellular processes [ 65 ].…”
Section: The Functional Properties Of Amyloids Assembled In Vitro or ...mentioning
confidence: 99%
“…The conversion of PrP C into PrP Sc is a post-translational process that is strictly dependent on the availability of the PrP C substrate. It is not known whether posttranslational modifications in PrP isoforms are causally involved in this process (Baskakov 2021). The infectious character of prions is well reflected in cell culture systems by the transfer of prion infectivity from cell to cell.…”
Section: Introductionmentioning
confidence: 99%